Exploring Teaching English Using ICT in Vietnam: The Lens of Activity Theory - Pham Thi To Nhu; Tan, Choon Keong; Lee, Kean Wah (2018)
The purpose of this qualitative study was to understand the activities and behaviours of teachers in teaching English using ICT. A total of 20 teachers of English from 4 different primary schools in different areas in Vietnam took part in this study. Data were collected through observations and focus group interviews. The findings were discussed based on Activity Theory. The lens of Activity Theory provides a versatile tool to inquire into various aspects of using ICT in teaching. The results indicated that teaching English using ICT in Vietnam had become much more popular than before and this fact had a certain effect. (69% of teachers were at Augmentation level and 31% at Modification level) Opportunities of bringing a good language environment to learners, getting instant feedback, giving learners interesting activities to practice language skills, and sharing designed activities with other teachers contributed to the advantages of using ICT in teaching. However, there were still some factors that limited the use of ICT in teaching English in Vietnam. Therefore, this study suggests the recommendations to better the situation.